Unusual case of primary spontaneous hemopneumothorax in a young man with atypical tension pneumothorax: a case report - Youwen Chen; Zhijian Guo (Journal of Medical Case Reports, 2018)
Abstract Background Spontaneous life-threatening hemopneumothorax is an atypical but treatable entity of unexpected circulatory collapse in young patients, affecting 0.5–11.6% of patients with primary spontaneous pneumothorax. Spontaneous pneumothorax is a well-documented disorder with a classic clinical presentation of acute onset chest pain and shortness of breath. This disorder might be complicated by the development of hemopneumothorax or tension pneumothorax. Case presentation A 23-year-old Asian man was referred to the emergency room of Xiamen Chang Gung Memorial Hospital with a 1-day history of right-sided chest pain that had been aggravated for 1 hour. A physical examination revealed a young man who was awake and alert but in mild to moderate painful distress. His vital parameters were relatively stable at first. The examining physician noted slight tenderness along the right posterolateral chest wall along the eighth and tenth ribs. Primary spontaneous pneumothorax was considered, and a standing chest X-ray confirmed the diagnosis. A right thoracostomy tube was immediately placed under sterile conditions, and he was referred to the respiratory service. While in the respiratory department, approximately 420 mL of blood was drained from the thoracostomy tube over 15 minutes. Our patient developed obvious hemodynamic instability with hypovolemic shock and was subsequently admitted to the cardiothoracic surgical ward after fluid resuscitation. During the ensuing 4 hours after admission, 750 mL of blood was drained through the thoracostomy tube. A bedside chest X-ray was requested after he was temporarily hemodynamically stabilized. Primary spontaneous hemopneumothorax associated with right tension pneumothorax was considered based on the radiological impression and clinical signs. An emergency limited posterolateral thoracotomy was performed. A standing chest X-ray performed on day 6 of admission after the removal of the thoracostomy tube showed a complete re-expansion of his right lung. He remained stable and was discharged within 1 week. Conclusions The successful treatment of a large spontaneous hemopneumothorax depends on early recognition, proactive intervention, and early consideration by a cardiothoracic surgeon. Once the diagnosis is confirmed, early thoracotomy should be considered. Such an aggressive surgery not only leads to shorter hospitalization but also confers better long-term outcomes.